Kedudukan Hukum Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 Terhadap Prinsip Kebebasan Hakim dalam Memutus Perkara - Girianto Edy Purnomo; Anang Dony Irawan (Universitas Muhammadiyah Yogyakarta, 2024)
This research aimed to examine the position of the Supreme Court Circular Letter, or hereinafter referred to SEMA, Number 2 of 2023 regarding the principle of Judges’ freedom in deciding cases. The method used normative juridical with a statutory approach. The primary, secondary and tertiary legal materials obtained analyzed using legal searches. The research results showed that SEMA’s legal position in the hierarchy of statutory regulations is below the law. Considering that the contents are contrary to the principle of freedom of judges in deciding cases in accordance with Article 3 Paragraph (1) and Elucidation of Article 3 Paragraph (1) of Law Number 48 of 2009 concerning Judicial Power, the existence of SEMA will also cause Judges to lose their freedom in deciding cases in the case of applications for registration of interfaith marriages, this will further be a dilemma for the judge when handling this case considering that the legal regulations regarding applications for interfaith marriages are also still valid and in force